2017
DOI: 10.1080/14728222.2017.1351949
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of SPAK kinase in disorders of impaired epithelial transport

Abstract: Introduction: The mammalian SPS1-related proline/alanine-rich serine-threonine kinase SPAK (STK39) modulates the transport across and between epithelial cells in response to environmental stimuli such osmotic stress and inflammation. Research over the last decade has established a central role for SPAK in the regulation of ion and water transport in the distal nephron, colonic crypts, and pancreatic ducts, and has implicated deregulated SPAK signaling in NaCl-sensitive hypertension, ulcerative colitis and Croh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…The Ste20-type Ser-Thr protein kinases SPAK (SPS1-related proline/alanine-rich kinase) and OSR1 (oxidative stressresponsive kinase 1) are considered master regulators of the CCCs 35 . SPAK and OSR1 are activated by phosphorylation in the regulatory "T-loop" (SPAK Thr233 and OSR1 Thr185) by one of four WNK ["with no lysine" (K)] protein kinases 17,36 .…”
mentioning
confidence: 99%
“…The Ste20-type Ser-Thr protein kinases SPAK (SPS1-related proline/alanine-rich kinase) and OSR1 (oxidative stressresponsive kinase 1) are considered master regulators of the CCCs 35 . SPAK and OSR1 are activated by phosphorylation in the regulatory "T-loop" (SPAK Thr233 and OSR1 Thr185) by one of four WNK ["with no lysine" (K)] protein kinases 17,36 .…”
mentioning
confidence: 99%
“…In previous studies, STK39 was demonstrated to activate the p38 MAPK pathway, which indicates that STK39 is involved in cellular stress responses (26). In addition, STK39 has been revealed to play a critical role in the regulation of ionic and osmotic cellular homeostasis (36,37). Recent studies have demonstrated that STK39 has carcinogenic functions in several cancer types (27)(28)(29).…”
Section: Discussionmentioning
confidence: 97%
“…The pharmacological targeting of SPAK includes antagonizing the SPAK-WNK interaction, inhibiting SPAK activity, or disrupting SPAK activation by interfering with its binding to Μ025α/β. These approaches could be useful for regulating the homeostasis of the renal epithelium and may have therapeutic potential for NaCl-sensitive hypertension [ 39 ]. In addition to the role in blood pressure regulation, abrogating SPAK activity may be a therapeutic strategy for other diseases.…”
Section: Discussionmentioning
confidence: 99%